The Contracts in Restraint of Trade in the English Law. A Comparative Study in the Iraqi Law - علي يونس صلاح الدين (Journal of Legal Sciences, 2021)
The contracts in restraint of trade are considered as void contracts according to the English common law, that is to say, they are prima facie void. Because their voidness is presumed and based upon a rebuttable presumption that these contracts are contrary to the public policy in principle. Owing to the unreasonableness of the Restraint of Trade conditions or terms in which they are included. But if it is proved that they satisfy the requirements of reasonableness, in accordance with the contracting parties, and both the temporal and spatial extent of their coming into effect, as well as the public interest. The court will validate them. It is also worth-bearing in mind that this type of contracts fall under contracts void at common law on the grounds of public policy, which are regarded as the second type of the void contracts in the English law. In addition to the first type represented by contract void by Statute. It is also worthmentioning that contracts in restraint of trade can be nullified or invalidated according to both the doctrine of Restraint of Trade and doctrine of illegality arising from the judicial precedents of English courts.